Urban Living Lab as an Education Strategy for Sustainable Development - Morales, Ivetheyamel; Segalás, Jordi; Masseck, Torsten (Espacio Abierto, 2024)
This study analyses the Delta Project, an Urban Living Lab (ULL) implemented at the Faculty of Architecture and Urbanism (FAU) of the University of Guayaquil (UG), as an innovative educational strategy for sustainable development. It highlights the challenges in architecture education, focusing on the need to adapt to the demands of sustainability and technological advances. ULLs, in response to these challenges, are presented as dynamic platforms that combine research, innovation and policy to promote sustainability in urban and educational contexts. The methodology employs a case study approach, detailing how the Delta Project is integrated as a learning environment at FAU and its relationship to sustainability goals and education for sustainable development (ESD). The E-ULL-HEIs tool was used to assess seven key indicators: objectives and scope, diversity and stakeholder participation, interdisciplinarity, curricular integration, learning and research impact, community impact, and resources and sustainability. Data were collected through semi-structured interviews, documentary analysis and participatory observation. The results indicate that FAU has successfully integrated the Delta Project into its educational programmes, highlighting its impact on diversity and stakeholder participation, interdisciplinarity, curricular integration, and learning and research. The findings underline the effectiveness of the Delta Project in promoting ESD and its alignment with the Sustainable Development Goals (SDGs). However, challenges were identified in terms of cross-sectoral collaboration and student participation, providing valuable lessons on the importance of strategic planning and adaptability. The study highlights the potential of the Delta Project model to be adapted and replicated in different cultural and academic contexts, suggesting the need for ongoing evaluations to improve the effectiveness of similar projects and promote ESD.